P–471 Preconception and infertility care across South America: availability of policy, guidelines, recommendations and services. (6th August 2021) - Mendonç. Carneiro, M; Gusmao, C; Nakano, F; Polisseni, F; Coutinho, L; Ferreira, M C
Abstract: Study question: What are the available preconception care policies, guidelines, recommendations and services as well as infertility care in South America ? Summary answer: Preconception recommendations offered by both governament and medical societies in South America were fragmented and inconsistent and public fertility care is available in seven countries. What is known already: Promoting preconception health can potentially improve women's health and pregnancy outcomes. Evidence-based interventions exist to reduce many maternal behaviors and chronic conditions that are associated with adverse pregnancy outcomes such as tobacco use, alcohol use, inadequate folic acid intake, obesity, hypertension, and diabetes. Paternal factors are also influence pregnancy outcomes but male preconcepction health has received little attention so far and he focus remains on women. Study design, size, duration: Cross-sectional evaluation including ann electronic search and investigation of preconception policy, guidelines, recommendations and services available to healthcare professionals and the general public in south America (N = 11 countries): Argentina, Bolívia, Brasil, Chile, Colômbia, Ecuador, , Paraguay, Peru, Suriname, Uruguay and Venezuela) that took place in June 2020. No ethical approval was obtained as we used only public avalialble online information. Participants/materials, setting, methods: Eleven South American countries) were included Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, , Paraguay, Peru, Suriname, Uruguay and Venezuela.we searched Google using advanced search setup for each country with the following words: Preconception care; Pre-pregnancy care; Before pregnancy; Conception; Pregnancy planning; Preconceptual and variations and Policy; Guidelines, Recommendations and services. Data from the Latin American Registry (REDLARA, 2017) and the Latin American Federation of Societies of Obstetrics and Gynecology (FLASOG) was also obtained . Main results and the role of chance: Government preconcepction care recommendations were available in 10 countries and 11 had family planning guidelines. Seven countries offered either public clinics or financial aid for infertile couples. According to REDLARA 2017 report there are 122 registered centers in South America but the region host much more. The Brazilian registry shows 154 IVF clinics in 2018. Although most countries offered guidance on major issues including folic acid supplementation (n = 10), nutrition (n = 10), Vaccination (n = 11), alcohol consumption (n = 11), smoking (n = 10), relevant health topics such physical activity (n = 7) and obesity (n = 7) were left out in 58, 3% of the countries. Medical societies provided guidelines on preconcpection care in 7 countries and for other health issues: folic acid supplementation (n = 5), nutrition (n = 5), Vaccination (n = 6), alcohol consumption (n = 4), smoking (n = 4), physical activity (n = 4)and obesity (n = 2). When male preconception care was considered, only two countries have public guidelines whereas no medical society provided specific recommendations for men. Sexually transmitted diseases (STD) was another topic of interest for both public (n = 10) and medical societies (n = 4). STD guidelines were heterogenous and focused more on treatment rather than prevention. FLASOG however displayed guidelines for peconception care and STD prevention. Limitations, reasons for caution: The search was performed only in Google as it is the most opular search engine. We did not include other search pages asuch as Yahoo and limited our search to the first 3 pages for each search term as people rarely examine more thatn the first there pages. Wider implications of the findings: Current reccomendations are heterogeneous, fragmented and inconsitent and there is a lack of interest on male reproductive health y. Public fertility care is only available in 7 countries. Collaborative research among countries is necessary so as to develop evidence-based guidelines for preconcepction and fertility care for both men and women. Trial registration number: not-applicable